Associations of Phoretic Mites on Bark Beetles of the Genus Ips in the Black Sea Mountains of Turkey - Cilbircioğlu, Cihan; Kovač, Marta; Pernek, Milan (MDPI AG, 2021)
Phoretic mites use bark beetles for transportation to new, suitable habitats. Some phoretic mites act as predators and parasitoids of the bark beetles’ immature stages, especially egg and early larval stages, and are potential agents for the biological control of scolytine forest pests. Mites live very frequently in relationships with other invertebrates. Many are found in association with various species of bark beetles. Here, a total of 41 specimens of different bark beetles of the genus Ips (Ips acuminatus, Ips sexdentatus and Ips typographus) were studied for presence, species composition, and abundance of phoretic mites. The beetles were collected on dead wood and parts of tree bark of Pinus nigra, Pinus sylvestris and Picea abies in the Black Sea Mountains in Kastamonu and Artin Province of Turkey. A total of nine mite species were found, including Dendrolaelaps quadrisetus, Ereynetes sp., Histiostoma piceae, Paraleius cf. leontonychus, Pleuronectocelaeno barbara., Proctolaelaps hystricoides, Schizostethus simulatrix, Trichouropoda lamellosa and Uroobovellaipidis. All species are identified for the first time within Turkish fauna.
Keywords: anatomy_morphology; 15. Life on land